Organizational Strategic Response in Implementing the Indonesian ISFAS 109 on Accounting for Zakat: Case of Amil Zakat Agency in Bali - Prayudi, Made Aristia; Sofyani, Hafiez (Faculty of Islamic Economics and Business of Institut Agama Islam Negeri (IAIN) Pekalongan, 2021)
This study addresses an issue of the alternative strategic responses, rather than compliance, to institutional pressure take by a public organization. This study aims to investigate why and how zakat management organizations strategically respond to comply or not to comply with the Indonesian Statement of Financial Accounting Standards of 109 (ISFAS 109) concerning Accounting for Zakat. This study was conducted in National Amil Zakat Agency in Bali, and it applies a case study method with interviews, observation, and document review as data collection techniques. The data were interactively analyzed by applying thematic analysis. The results showed that although a majority of the financial reporting processes could reflect the choice of acquiescence responses (compliance) to the ISFAS 109, other findings revealed the existence of non-compliance responses (compromise-balancing). These non-compliance responses were relating to the context of receiving non-halal funds and the related parties' transactions. It is also found that the existence of this non-compliance behavior can be attributed to the low level of both organizational dependence on its constituents and coercivity of the institutional pressure. This study contributes theoretically by revealing new findings of a significant role of powerful internal actor in shaping the organizational response to institutional pressure. Besides, it have practical implications on policy formulation by the Indonesian Accounting Association as a standard-setter body.